Perovskite / TOPCon laminated cell and bottom cell and preparation method thereof
By performing laser propulsion and post-oxidation treatment in the perovskite/TOPCon stacked battery base cell, the doping degree of non-metallic contact area is reduced and the passivation contact structure is formed, the problems of low filling and low photoelectric conversion efficiency of the base cell are solved, and a higher photoelectric conversion efficiency is achieved.
Patent Information
- Application Number
- CN202510090884.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-25
AI Technical Summary
The perovskite/TOPCon stacked battery has problems such as high non-metal contact area composite, poor contact area contact, low filling and low photoelectric conversion efficiency.
By double-sided velvet making of the silicon wafer, preparing a boron-doped layer on the first surface and laser propulsion and post-oxidation treatment, the doping degree of the non-metallic contact region is reduced, and a tunneled oxide layer and an intrinsic polysilicon layer are deposited on the second surface to form a passivation contact structure.
It improves the short-wave response of sunlight, reduces contact resistance, improves current, open voltage and filling, and thus improves the photoelectric conversion efficiency of perovskite/TOPCon stacked batteries.
Smart Images

Figure CN119894147A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of solar cells, and in particular relates to a perovskite / TOPCon stacked cell and a bottom cell thereof and a preparation method thereof. Background Art
[0002] The research progress of perovskite-silicon-based tandem cells is rapid. At present, the highest efficiency of a single perovskite-silicon-based tandem cell has exceeded 33%. Perovskite / TOPCon tandem cells are stacked with TOPCon cells and perovskite solar cells to ensure the complete process of the boron diffusion surface part, remove the passivation layer and metal electrode in the preparation process of the phosphorus diffusion surface, and use the TOPCon cell inverted as the bottom cell. This scheme is currently a common preparation method for perovskite / TOPCon bottom cells. In order to ensure that the contact resistance of the first surface metal contact area is low, the emitter adopts a high doping concentration and a high driving depth diffusion. The uniform emitter bottom cell obtained in this way has the problems of high recombination of the non-metallic contact area, low filling and low photoelectric conversion efficiency. In addition, the cell size of the perovskite tandem cell is often prepared in the size of 1cm×1cm, 3.8cm×3.8cm or larger, and the grid line pattern is often adopted as a grid grid line pattern. Therefore, laser sintering technology cannot be applied to small perovskite cells at present, and the problem of large recombination of the non-metallic contact area of the emitter cannot be solved.
[0003] The tunnel oxide passivated contact solar cell (TOPCon) with homojunction structure is prepared by preparing an ultra-thin tunnel oxide layer and a highly doped polysilicon thin layer on the second surface of the bottom cell. The two together form a passivated contact structure, which can effectively block the recombination of minority carriers and holes, thereby improving the open circuit voltage and short circuit current of the cell. The first surface of the TOPCon bottom cell is usually prepared with a boron emitter to form a PN junction, and then a metal electrode is printed. In order to ensure that the Ag / Al Finger is in contact with the emitter, the TOPCon bottom cell prepared in this way often has the problem of high boron emitter doping concentration and high body concentration in the non-metallic contact area, which leads to high body recombination of the bottom cell, low filling and low photoelectric conversion efficiency, which in turn leads to low photoelectric conversion efficiency of the entire stacked cell. Therefore, how to ensure that the stacked solar cell has the characteristics of high photoelectric conversion efficiency and simple preparation process while having a simple structure and low cost has become an urgent problem to be solved.
[0004] The patent with publication number CN112736200A discloses a stacked cell and its preparation method and application. The stacked cell uses a perovskite solar cell as a top cell and a polycrystalline silicon cell as a bottom cell, and the top cell and the bottom cell are connected in series through a composite layer; the stacked cell includes, from top to bottom, a front metal grid electrode, an anti-reflection film layer, a transparent conductive film layer, an intermediate protective layer, an electron transport layer, a passivation layer, a perovskite absorption layer, a molecular ferroelectric layer, a perovskite hole transport layer, a composite layer, a crystalline silicon cell and a back electrode. The patent with publication number CN113851554A discloses that the preparation method specifically includes: preparing an emitter on the front of a silicon substrate, and sequentially preparing a back tunneling layer, a back doped polycrystalline silicon layer, a back passivation layer and a back metal electrode on the back of the silicon substrate to obtain a bottom cell; sequentially preparing a hole transport layer, a perovskite layer, an electron transport layer, an electrode buffer layer, a transparent electrode and a metal electrode on the surface of the composite layer to obtain the stacked cell. The preparation of these disclosed crystalline silicon / perovskite stacked cell pairs and the emitter on the first surface all adopts a simple one-step diffusion, deposition of a passivation layer, and printing of a metal electrode. The TOPCon bottom cell prepared by this preparation method has a high boron diffusion temperature, and there are problems such as high body recombination in the non-metallic contact area, poor contact in the metal contact area, low filling of the overall stacked cell, and low photoelectric conversion efficiency. Summary of the invention
[0005] Based on this, the purpose of the present invention is to provide a perovskite / TOPCon stacked cell and its bottom cell and preparation method, which have solved the problems in the prior art of high body recombination in the non-metallic contact area, poor contact in the metal contact area, low filling of the overall stacked cell and low photoelectric conversion efficiency.
[0006] To achieve the above object, the present invention adopts the following technical solution.
[0007] The present invention provides a method for preparing a bottom cell of a perovskite / TOPCon stacked cell, comprising:
[0008] Step 1: Double-sided texturing of the silicon wafer;
[0009] Step 2, preparing a boron-doped layer on the first surface of the silicon wafer;
[0010] Step 3, laser propulsion is performed on the metal contact area on the boron-doped layer to achieve heavy doping of the metal contact area; oxygen is then injected for post-oxidation, and after the post-oxidation is completed, the plating on the second surface of the silicon wafer is removed; after the post-oxidation is completed, the diffusion square resistance of the metal contact area is 250Ω / SP~400Ω / SP, and the diffusion square resistance of the non-metal contact area is 150Ω / SP~250Ω / SP;
[0011] Step 4: After step 3, the silicon wafer is subjected to secondary texturing; a tunnel oxide layer and an intrinsic polysilicon layer are sequentially deposited on the second surface of the silicon wafer, and a phosphorus-doped layer is prepared on the intrinsic polysilicon layer; then, the first surface of the silicon wafer is de-poly plated and cleaned, and a passivation film layer and an anti-reflection film layer are deposited on the first surface and the second surface of the silicon wafer;
[0012] Step five: print AgAl paste on the front anti-reflection film layer on the first surface, form a metal electrode after sintering, and obtain a TOPCon perovskite stacked battery bottom cell.
[0013] In the present invention, the doping degree of the non-metallic contact area on the perovskite / TOPCon stacked bottom cell is reduced, thereby reducing the recombination of the diffusion layer in the non-contact area, thereby improving the short-wave response of sunlight and solving the problems of low filling of the bottom cell and low photoelectric conversion efficiency; at the same time, laser propulsion is used in the contact area to increase the diffusion concentration and junction depth, thereby reducing the contact resistance between the metal electrode and the emitter region, so that the current, opening voltage and filling are all improved, further improving the conversion efficiency of the perovskite / TOPCon stacked cell.
[0014] In some embodiments of the present invention, the diffusion sheet resistance of the boron-doped layer is 100-200Ω / SP.
[0015] In some embodiments of the present invention, when preparing the boron doped layer, the diffusion temperature is 500°C to 900°C.
[0016] In some embodiments of the present invention, in laser propulsion, the parameters of the laser are set as follows: output power 10W to 100W, pulse repetition frequency 200kHz to 150kHz, laser spot diameter 5Pm to 40Pm and laser beam speed 10000mm / s to 30000mm / s. Too low output power will lead to insufficient diffusion depth in the non-contact area, while too high output power will lead to excessive diffusion depth and introduce lattice damage; too low pulse repetition frequency will lead to insufficient doping concentration and diffusion depth, while too high output power will lead to excessive diffusion concentration and doping depth.
[0017] In some embodiments of the present invention, the diffusion sheet resistance of the metal contact region after laser advancement is 200Ω / SP to 350Ω / SP.
[0018] In some embodiments of the present invention, the oxidation temperature in the post-oxidation is 800°C to 1100°C.
[0019] In some embodiments of the present invention, in the post-oxidation, the oxidation time is 3000s to 6000s.
[0020] In some embodiments of the present invention, the thickness of the tunnel oxide layer is 1 nm to 5 nm; the thickness of the intrinsic polysilicon film is 20 nm to 300 nm.
[0021] In some embodiments of the present invention, the thickness of the passivation film layer is 30 nm to 100 nm; the thickness of the anti-reflection film layer is 10 nm to 50 nm.
[0022] In some embodiments of the present invention, the height of the velvet surface after secondary texturing is 0.5 to 0.9 μm. The light trapping of the second surface of the silicon wafer can be increased by secondary texturing. If the velvet surface height is too high, it may cause excessive reflection of light at the top of the velvet surface, making it difficult for light to enter the interior of the silicon wafer, which in turn reduces the light trapping effect. On the other hand, too high a velvet surface will make the subsequent coating of the perovskite layer uneven or even unable to cover; resulting in reduced battery opening voltage and filling, affecting battery efficiency. Moreover, an excessively high velvet surface structure will increase the specific surface area of the silicon wafer, leading to an increase in the number of surface recombination centers and an increase in the probability of carrier recombination on the surface, thereby reducing the open circuit voltage and short-circuit current density of the battery, and having a negative impact on the overall performance of the battery. If the velvet surface height is too low, the velvet surface structure on the surface of the silicon wafer is too flat, the number of light reflections on the surface of the silicon wafer is relatively small, most of the light will be directly reflected out, the light absorption efficiency cannot be effectively improved, and the light trapping effect cannot be fully exerted. In particular, the absorption effect of long-wave light is poor, and it is difficult to meet the requirements of high-efficiency solar cells for light trapping effects.
[0023] In some embodiments of the present invention, the secondary texturing is performed using a low-concentration alkali solution; the concentration of the low-concentration alkali solution is 2-3wt%; the texturing time is 90-100s; and the texturing temperature is 55-60°C. For example, the concentration of the low-concentration alkali solution is 2wt%, 2.5wt% or 3wt%; the texturing time is 90s, 95s, 100s; and the texturing temperature is 55°C, 56°C, 57°C, 58°C, 59°C or 60°C.
[0024] During the secondary texturing process, if the concentration of alkali solution is too high, the chemical reaction between alkali solution and silicon will be too strong, which will affect the mechanical strength of silicon wafers and make silicon wafers more easily damaged, thus affecting the overall performance of the battery. Too long or insufficient texturing time will also cause the surface of silicon wafers to be damaged or the corrosion degree of silicon wafer surface is insufficient, and the ideal velvet surface cannot be formed. The texturing temperature will significantly affect the formation of the velvet structure on the surface of silicon wafers. When the temperature is low, the chemical reaction rate of alkali solution and silicon is slow, and the corrosion of silicon wafer surface is relatively uniform but slow, which may lead to the formation of velvet structure with small size and low height, and the density of velvet surface is not ideal. Such velvet structure has limited ability to scatter and absorb light, which is not conducive to improving the light trapping effect of silicon wafers. As the temperature rises, the chemical reaction rate accelerates, the corrosion of silicon wafer surface intensifies, and a velvet structure with moderate size, height and density can be formed, which is conducive to increasing the propagation path of light in silicon wafers and improving the light absorption efficiency, thereby improving the photoelectric conversion performance of solar cells. However, if the temperature is too high and the reaction is too intense, the velvet structure may become irregular and excessive corrosion may occur, resulting in poor consistency of the velvet, which in turn reduces the light trapping effect and leads to a decline in battery performance.
[0025] The present invention also provides a bottom cell of the perovskite / TOPCon stacked cell prepared by the preparation method.
[0026] The present invention also provides a perovskite / TOPCon stacked cell, comprising the bottom cell.
[0027] In some embodiments of the present invention, the TOPCon perovskite stacked cell includes, from top to bottom, a front metal grid electrode Ag, an anti-reflection film layer SiNx, a transparent conductive layer ITO, an electron transport layer SnO2, a perovskite layer, a hole transport layer TiO2, a carrier recombination layer ITO and a bottom cell.
[0028] In some embodiments of the present invention, the thickness of the anti-reflection film layer is 10nm to 70nm, the thickness of the transparent conductive layer is 80nm to 100nm, the thickness of the electron transport layer is 15nm to 40nm, the thickness of the perovskite layer is 800nm to 1200nm, the thickness of the hole transport layer is 30nm to 100nm, and the thickness of the carrier recombination layer is 80nm to 100nm.
[0029] Based on the technical solution of the present invention, compared with the prior art, the present invention has the following beneficial effects: in the present invention, the bottom cell of the perovskite / TOPCon stacked cell is firstly changed, specifically by reducing the doping concentration of the non-metallic contact area, thereby reducing the recombination of the diffusion layer in the non-metallic contact area, thereby improving the short-wave response of sunlight, and solving the problems of low filling of the bottom cell and low photoelectric conversion efficiency; at the same time, the contact area is promoted by laser to increase the diffusion concentration and junction depth, thereby reducing the contact resistance between the metal electrode and the emitter region, so that the current, opening voltage and filling are all improved.
[0030] In the present invention, the prepared bottom cell is used to prepare a perovskite / TOPCon stacked cell, further improving the conversion efficiency of the TOPCon perovskite stacked cell. Secondly, the laser propulsion technology solves the obstacle that the existing laser sintering technology cannot be applied to small perovskite cells. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 Flow chart for the preparation of the bottom cell of the perovskite / TOPCon stacked cell.
[0032] Figure 2 Schematic diagram of the structure of the bottom cell of the selective emitter perovskite / TOPCon stacked cell.
[0033] Figure 3 Schematic diagram of the structure of perovskite / TOPCon stacked cells. DETAILED DESCRIPTION
[0034] The experimental methods in the following examples of the present invention without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturers.
[0035] Unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0036] The terms "including" and "having" and any variations thereof of the present invention are intended to cover non-exclusive inclusions. For example, a process, method, device, product or equipment comprising a series of steps is not limited to the listed steps or modules, but may optionally include steps not listed, or may optionally include other steps inherent to these processes, methods, products or equipment.
[0037] In the present invention, the term "multiple" refers to two or more than two. "And / or" describes the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent the following three situations: A exists alone, A and B exist at the same time, and B exists alone. The character " / " generally indicates that the associated objects are in an "or" relationship.
[0038] The following describes the invention in conjunction with specific embodiments.
[0039] Example 1
[0040] 1. A method for preparing a bottom cell of a perovskite / TOPCon stacked cell (schematic diagram of the preparation process as shown in FIG. Figure 1 shown), including:
[0041] S1 texturing: using low concentration alkaline solution etching, a pyramid structure of uniform size is formed on both sides of the silicon wafer (N-type single crystal silicon wafer, resistivity range of 1.0 ~ 7.0 / (Ω × m), thickness of 100 ~ 200μm, size of 182 × 183.75mm); the low concentration of alkaline solution is controlled at 1wt%, the texturing time is controlled at 500s, the texturing temperature is controlled at 65℃, and the height is 1.2μm;
[0042] S2 Boron Diffusion: Use BCl3 as a diffusion source to diffuse on the first surface of the silicon wafer to lightly dope the emitter; the diffusion temperature is 500℃, and the diffusion square resistance is controlled at 200Ω / SP;
[0043] S3 laser propulsion: laser propulsion is performed on the metal contact area according to the grid line pattern of the perovskite stacked cell to achieve heavy doping of the metal contact area, and the diffusion square resistance is controlled at 300Ω / SP. The laser parameters are set as follows: output power 10W, pulse repetition frequency 200kHz, laser spot diameter 5Pm and laser beam speed 10000mm / s;
[0044] S4 post-oxidation: low-temperature oxygen injection is used to improve diffusion uniformity, the oxidation temperature is 800°C, and the oxidation time is 3000s; after the post-oxidation, the diffusion square resistance of the metal contact area is controlled at 350Ω / SP, and the diffusion square resistance of the non-metal contact area is controlled at 200Ω / SP;
[0045] S5: removing the second surface plating: removing the second surface plating by using high concentration HF; wherein the concentration of HF is controlled at 5wt%;
[0046] S6 Secondary texturing to prepare small velvet on the second surface: using low-concentration alkaline solution to etch, small pyramid structures of uniform size are formed on both sides of the silicon wafer, and the velvet height is controlled at 0.5μm; the low-concentration alkaline solution is controlled at 2wt%, the texturing time is controlled at 100s, and the texturing temperature is controlled at 60℃;
[0047] S7 Tunneling oxide layer and intrinsic polysilicon layer: using LPCVD technology, deposit a tunneling oxide layer with a thickness of 1 nm on the second surface; and continue to deposit an intrinsic polysilicon film with a thickness of 20 nm on the tunneling oxide layer to form an intrinsic polysilicon layer;
[0048] S8 Phosphorus diffusion: Using POCl3 as a diffusion source, phosphorus is diffused in the intrinsic polysilicon layer to form a phosphorus-doped layer; the diffusion temperature is 700℃ and the doping concentration is 1E20cm -3 ;
[0049] S9: Remove the first surface wrap plating and clean: Use high concentration HF to remove the back wrap plating; use HF / H2O2 and NH3 / H2O2 as cleaning solution to clean the silicon wafer; the concentration of HF / H2O2 is controlled at 5wt%;
[0050] S10 Deposition of AlOx / SiNx film layer: A layer of AlOx film is deposited on the boron-doped surface by ALD atomic deposition method, and the thickness of the AlOx film is 6nm. Then, a SiNx film layer is deposited on the AlOx film of the silicon wafer by PECVD, and the thickness of the SiNx film layer is 90nm, finally forming a passivation film layer; SiONx is deposited on the silicon wafer by PECVD, and the thickness of the SiONx film layer is 10nm to form an anti-reflection film layer;
[0051] S11 printing: AgAl paste is printed on the first surface of the silicon wafer, and a metal electrode is formed after sintering. The bottom cell structure is as follows Figure 2 shown.
[0052] A perovskite / TOPCon stacked battery, comprising, from top to bottom: a front metal grid electrode Ag, an anti-reflection film layer with a thickness of 40nm, a transparent conductive layer with a thickness of 80nm, an electron transport layer with a thickness of 15nm, a perovskite layer with a thickness of 800nm, a hole transport layer with a thickness of 30nm, a carrier recombination layer with a thickness of 80nm and a bottom battery.
[0053] The above-mentioned perovskite / TOPCon stacked cell in this embodiment is prepared by the following steps: using the TOPCon bottom cell prepared in this embodiment; using 5wt% HF to remove the SiNx film layer on the second surface; then using PVD magnetron sputtering equipment to prepare a layer of 80nm thick ITO material as a carrier recombination layer on the second surface of the TOPCon bottom cell; then using spray thermal decomposition method to prepare a 30nm thick TiO2 material as a hole transport layer on the carrier recombination layer; then using spin coating to prepare a calcium The titanium ore film layer is 800nm, and the perovskite material structure is ABX3, wherein A is any one of methylamine, formamidine, Cs or a mixture of several cations, B is Pb or Sn, and X is any one of Cl, Br, I or a mixture of three anions; then, a 15nm thick SnO2 material is prepared on the perovskite film layer by spin coating as an electron transport layer; then, an 80nm thick ITO material is prepared on the electron transport layer by PVD magnetron sputtering as a transparent conductive oxide layer; finally, a 40nm thick SiN x The film layer is printed with AgAl paste on the front side of the stack, and the front metal electrode is formed after sintering to obtain a perovskite / TOPCon stacked battery. The structure of the perovskite / TOPCon stacked battery is as follows Figure 3 shown.
[0054] Example 2
[0055] Compared with Example 1, the difference is that the preparation method of the bottom battery is different, and the other steps are the same. The steps of the bottom battery in this embodiment are specifically as follows:
[0056] S1 texturing: using low concentration alkaline solution etching, a pyramid structure of uniform size is formed on both sides of the silicon wafer (N-type single crystal silicon wafer, resistivity range is 1.0-7.0 / (Ω×m), thickness is 100-200μm, size is 182×183.75mm); the low concentration of alkaline solution is controlled at 2wt%, the texturing time is controlled at 500s, the texturing temperature is controlled at 70℃, and the height is 1.2μm;
[0057] S2 Boron Diffusion: Use BCl3 as a diffusion source to diffuse on the first surface of the silicon wafer to lightly dope the emitter; the diffusion temperature is 500℃, and the diffusion square resistance is controlled at 100Ω / SP;
[0058] S3 laser propulsion: laser propulsion is performed on the metal contact area according to the grid line pattern of the perovskite stacked battery to achieve heavy doping of the metal contact area, and the diffusion square resistance is controlled at 200Ω / SP. The laser parameters are set as follows: output power 10W, pulse repetition frequency 200kHz, laser spot diameter 5Pm and laser beam speed 10000mm / s;
[0059] S4 post-oxidation: low-temperature oxygen injection is used to improve diffusion uniformity, the oxidation temperature is 800°C, and the oxidation time is 4500s; the diffusion square resistance of the metal contact area is controlled at 250Ω / SP, and the diffusion square resistance of the non-metal contact area is controlled at 150Ω / SP;
[0060] S5: removing the second surface plating: removing the second surface plating by using high concentration HF; wherein the concentration of HF is controlled at 5wt%;
[0061] S6 Secondary texturing to prepare small velvet on the second surface: using low-concentration alkaline solution to etch, small pyramid structures of uniform size are formed on both sides of the silicon wafer, and the velvet height is controlled at 0.7μm; the low-concentration alkaline solution is controlled at 2wt%, the texturing time is controlled at 100s, and the texturing temperature is controlled at 60℃;
[0062] S7 Tunneling oxide layer and intrinsic polysilicon layer: using LPCVD technology, deposit a tunneling oxide layer with a thickness of 1 nm on the second surface; and continue to deposit an intrinsic polysilicon film with a thickness of 20 nm on the tunneling oxide layer to form an intrinsic polysilicon layer;
[0063] S8 Phosphorus diffusion: Using POCl3 as a diffusion source, phosphorus is diffused in the intrinsic polysilicon layer to form a phosphorus-doped layer; the diffusion temperature is 700℃ and the doping concentration is 1E20cm -3 ;
[0064] S9: Remove the first surface wrap plating and clean: Use high concentration HF to remove the back side wrap plating; Use HF / H2O2 and NH3 / H2O2 cleaning solution to clean the silicon wafer;
[0065] S10 Deposition of AlOx / SiNx film layer: A layer of AlOx film is deposited on the boron-doped surface by ALD atomic deposition method, and the thickness of the AlOx film is 6nm. Then, a SiNx film layer is deposited on the AlOx film of the silicon wafer by PECVD, and the thickness of the SiNx film layer is 90nm, finally forming a passivation film layer; SiONx is deposited on the silicon wafer by PECVD, and the thickness of the SiONx film layer is 30nm to form an anti-reflection film layer;
[0066] S11 printing: AgAl paste is printed on the first surface of the silicon wafer, and a metal electrode is formed after sintering. The bottom cell structure is as follows Figure 2 shown.
[0067] Example 3
[0068] Compared with Example 1, the difference is that the preparation method of the bottom battery is different, and the other steps are the same. The steps of the preparation method of the bottom battery in this embodiment are specifically as follows:
[0069] S1 texturing: using low concentration alkaline solution etching, a pyramid structure of uniform size is formed on both sides of the silicon wafer (N-type single crystal silicon wafer, resistivity range is 1.0-7.0 / (Ω×m), thickness is 100-200μm, size is 182×183.75mm); the low concentration of alkaline solution is controlled at 3wt%, the texturing time is controlled at 500s, the texturing temperature is controlled at 75℃, and the height is 1.2μm;
[0070] S2 Boron Diffusion: Use BCl3 as a diffusion source to diffuse on the first surface of the silicon wafer to lightly dope the emitter; the diffusion temperature is 500℃, and the diffusion square resistance is controlled at 150Ω / SP;
[0071] S3 laser propulsion: laser propulsion is performed on the metal contact area according to the grid line pattern of the perovskite stacked cell to achieve heavy doping of the metal contact area, and the diffusion square resistance is controlled at 350Ω / SP. The laser parameters are set as follows: output power 10W, pulse repetition frequency 200kHz, laser spot diameter 5Pm and laser beam speed 10000mm / s;
[0072] S4 post-oxidation: low-temperature oxygen injection is used to improve diffusion uniformity, the oxidation temperature is 800°C, and the oxidation time is 6000s; the diffusion square resistance of the metal contact area is controlled at 400Ω / SP, and the diffusion square resistance of the non-metal contact area is controlled at 250Ω / SP;
[0073] S5: removing the second surface plating: removing the second surface plating by using high concentration HF; wherein the concentration of HF is controlled at 5wt%;
[0074] S6 Secondary texturing to prepare small velvet on the second surface: using low-concentration alkaline solution to etch, small pyramid structures of uniform size are formed on both sides of the silicon wafer, and the velvet height is controlled at 0.9μm; the low-concentration alkaline solution is controlled at 3wt%, the texturing time is controlled at 200s, and the texturing temperature is controlled at 70℃;
[0075] S7 Tunneling oxide layer and intrinsic polysilicon layer: using LPCVD technology, deposit a tunneling oxide layer with a thickness of 1 nm on the second surface; and continue to deposit an intrinsic polysilicon film with a thickness of 20 nm on the tunneling oxide layer to form an intrinsic polysilicon layer;
[0076] S8 Phosphorus diffusion: Using POCl3 as a diffusion source, phosphorus is diffused in the intrinsic polysilicon layer to form a phosphorus-doped layer; the diffusion temperature is 700℃ and the doping concentration is 1E20cm -3 ;
[0077] S9: Remove the first surface wrap plating and clean: Use high concentration HF to remove the back side wrap plating; Use HF / H2O2 and NH3 / H2O2 cleaning solution to clean the silicon wafer;
[0078] S10 Deposition of AlOx / SiNx film layer: A layer of AlOx film is deposited on the boron-doped surface by ALD atomic deposition method, and the thickness of the AlOx film is 6nm. Then, a SiNx film layer is deposited on the AlOx film of the silicon wafer by PECVD, and the thickness of the SiNx film layer is 90nm, finally forming a passivation film layer; SiONx is deposited on the silicon wafer by PECVD, and the thickness of the SiONx film layer is 50nm to form an anti-reflection film layer;
[0079] S11 printing: AgAl paste is printed on the first surface of the silicon wafer, and a metal electrode is formed after sintering. The bottom cell structure is as follows Figure 2 shown.
[0080] Example 4
[0081] Compared with Example 1, the difference is that the preparation method of the perovskite / TOPCon stacked battery is different, and the other methods are the same. In this embodiment, the structure and preparation method of the perovskite / TOPCon stacked battery are specifically described as follows:
[0082] A perovskite / TOPCon stacked cell, comprising, from top to bottom: a front metal grid electrode Ag, an anti-reflection film layer (10 nm thick), a transparent conductive layer (90 nm thick), an electron transport layer (25 nm thick), a perovskite layer (1000 nm thick), a hole transport layer (60 nm thick), a carrier recombination layer (90 nm thick) and a bottom cell.
[0083] The above-mentioned perovskite / TOPCon stacked cell in this embodiment is prepared by the following steps: using the TOPCon bottom cell prepared in this embodiment; removing the SiNx film layer on the second surface by using 15wt% HF; then using PVD magnetron sputtering equipment to prepare a 90nm thick ITO material as a carrier recombination layer on the second surface of the TOPCon bottom cell; then using spray thermal decomposition method to prepare a 60nm thick TiO2 material as a hole transport layer on the carrier recombination layer; then using spin coating to prepare a calcium The titanium ore film layer is 1000nm, and the perovskite material structure is ABX3, wherein A is any one of methylamine, formamidine, Cs or a mixture of several cations, B is Pb or Sn, and X is any one of Cl, Br, I or a mixture of three anions; then, a 25nm thick SnO2 material is prepared on the perovskite film layer by spin coating as an electron transport layer; then, a 90nm thick ITO material is prepared on the electron transport layer by PVD magnetron sputtering as a transparent conductive oxide layer; finally, a 10nm thick SiN xThe film layer is printed with AgAl paste on the front of the stack, and the front metal electrode is formed after sintering to obtain the perovskite TOPCon stacked battery. The structure of the perovskite TOPCon stacked battery is as follows Figure 3 shown.
[0084] Example 5
[0085] Compared with Example 1, the difference is that the preparation method of the perovskite / TOPCon stacked battery is different, and the other methods are the same. In this embodiment, the structure and preparation method of the perovskite / TOPCon stacked battery are specifically described as follows:
[0086] A perovskite / TOPCon stacked battery, comprising, from top to bottom: a front metal grid electrode Ag, an anti-reflection film layer with a thickness of 70nm, a transparent conductive layer with a thickness of 100nm, an electron transport layer with a thickness of 40nm, a perovskite layer with a thickness of 1200nm, a hole transport layer with a thickness of 100nm, a carrier recombination layer with a thickness of 100nm and a bottom battery.
[0087] The above-mentioned perovskite / TOPCon stacked cell in this embodiment is prepared by the following steps: using the TOPCon bottom cell prepared in this embodiment; using 20wt% HF to remove the SiNx film layer on the second surface; then using PVD magnetron sputtering equipment to prepare a 100nm thick ITO material as a carrier recombination layer on the second surface of the TOPCon bottom cell; then using spray thermal decomposition method to prepare a 100nm thick TiO2 material as a hole transport layer on the carrier recombination layer; then using spin coating to prepare The perovskite film layer is 1200nm, and the perovskite material structure is ABX3, wherein A is any one of methylamine, formamidine, Cs or a mixture of several cations, B is Pb or Sn, and X is any one of Cl, Br, I or a mixture of three anions; then, a 40nm thick SnO2 material is prepared on the perovskite film layer by spin coating as an electron transport layer; then, a 100nm thick ITO material is prepared on the electron transport layer by PVD magnetron sputtering as a transparent conductive oxide layer; finally, a 70nm thick SiN is deposited on the front by PECVD x The film layer is printed with AgAl paste on the front side of the stack, and the front metal electrode is formed after sintering to obtain a perovskite / TOPCon stacked battery. The structure of the perovskite / TOPCon stacked battery is as follows Figure 3 shown.
[0088] Comparative Example 1
[0089] Compared with Example 1, the difference in the preparation method of Comparative Example 1 is that in the preparation method of the bottom cell, the method of S2 boron diffusion is different, and the other steps are the same. Specifically, in Comparative Example 1, the boron diffusion step is: using BCl3 as a diffusion source to diffuse on the back side of the silicon wafer to lightly dope the emitter; the diffusion temperature is 500°C, and the diffusion square resistance is controlled at 300Ω / SP.
[0090] Comparative Example 2
[0091] Compared with Example 1, the difference in the preparation method of Comparative Example 2 is that in the preparation method of the bottom cell, the method of S2 boron diffusion is different, and the other steps are the same. Specifically, in Comparative Example 2, the boron diffusion step is: using BCl3 as a diffusion source to diffuse on the back side of the silicon wafer to lightly dope the emitter; the diffusion temperature is 1000°C, and the diffusion square resistance is controlled at 150Ω / SP.
[0092] Comparative Example 3
[0093] Compared with Example 1, the difference in the preparation method of Comparative Example 3 is that in the preparation method of the bottom cell, the parameters of S3 laser propulsion are different, and the other steps are the same. Specifically, in Comparative Example 3, the step of laser propulsion is: using a laser to propel the metal contact area according to the grid line pattern of the perovskite stacked cell to achieve heavy doping of the metal contact area. The parameters of the laser are set as follows: output power 200W, pulse repetition frequency 200kHz, laser spot diameter 5Pm and laser beam speed 10000mm / s.
[0094] Comparative Example 4
[0095] Compared with Example 1, the difference in the preparation method of Comparative Example 4 is that in the preparation method of the bottom battery, the S3 laser propulsion step is cancelled, and the remaining steps are the same.
[0096] Comparative Example 5
[0097] Compared with Example 1, the difference in the preparation method of Comparative Example 5 is that in the preparation method of the bottom cell, the parameters of S4 post-oxidation are different, and the other steps are the same. Specifically, in Comparative Example 5, the step of S4 post-oxidation is: using low-temperature oxygen injection to improve diffusion uniformity, the oxidation temperature is 600°C, and the post-oxidation square resistance is controlled at 150Ω / SP.
[0098] Comparative Example 6
[0099] Compared with Example 1, the difference in the preparation method of Comparative Example 6 is that in the preparation method of the bottom cell, the parameters of S4 post-oxidation are different, and the other steps are the same. Specifically, in Comparative Example 6, the step of S4 post-oxidation is: using low-temperature oxygen injection to improve diffusion uniformity, the oxidation temperature is 800°C, and the post-oxidation square resistance is controlled at 450Ω / SP.
[0100] Perovskite / TOPCon stacked cells were prepared using the preparation methods provided in Examples 1 to 5 and Comparative Examples 1 to 6, and the performance of the perovskite / TOPCon stacked cells was measured. The results are shown in Table 1.
[0101] Table 1 Test results of battery performance of Examples 1 to 5 and Comparative Examples 1 to 6
[0102] Preparation method Eta(%) Uoc(V) Isc(A) FF(%) Example 1 29.51 1.753 25.86 76.91 Example 2 27.52 1.739 24.69 76.71 Example 3 25.38 1.718 23.16 75.36 Example 4 26.55 1.733 24.95 72.56 Example 5 25.46 1.724 23.06 75.67 Comparative Example 1 23.86 1.603 21.32 75.11 Comparative Example 2 22.06 1.726 20.69 72.99 Comparative Example 3 21.26 1.713 20.13 70.36 Comparative Example 4 20.18 1.678 21.56 65.08 Comparative Example 5 22.49 1.710 22.12 70.26 Comparative Example 6 19.99 1.612 19.36 75.69
[0103] Note: In the table, Eta (efficiency) indicates the ratio of solar energy converted into electrical energy by the cell; Uoc indicates open circuit voltage; Isc indicates short circuit current; FF indicates fill factor.
[0104] As can be seen from Table 1, the conversion efficiency of the TOPCon perovskite tandem cells prepared by the preparation methods provided in Examples 1 to 5 is higher than that of Comparative Examples 1 to 5. It can be seen that the methods provided in Examples 1 to 5 of the present invention can prepare perovskite / TOPCon tandem cells with higher conversion efficiency.
[0105] As shown in Table 1, compared with Example 1, the boron diffusion resistance of Comparative Example 1 is different, and the opening voltage and current parameters of the prepared perovskite / TOPCon stacked battery are lower than those of Example 1. It can be seen that when the diffusion resistance becomes larger, the impact on the current is large, resulting in a decrease in the conversion efficiency of the prepared perovskite / TOPCon stacked battery. When the temperature of boron diffusion is too high, the opening voltage, current and filling will all be reduced, which will also reduce the conversion efficiency of the perovskite stacked battery.
[0106] Compared with Example 1, the parameters of laser propulsion are set differently in Comparative Example 3. It can be seen that too high output power will lead to too high doping concentration and too deep doping depth, which will reduce the opening voltage, current and filling of the perovskite stacked cell.
[0107] Compared with Example 1, when laser doping is not used in Comparative Example 4, insufficient doping is caused, resulting in reduced filling of the perovskite tandem cell.
[0108] Compared with Example 1, the post-oxidation temperature or post-oxidation square resistance of Comparative Examples 5 and 6 is different. It can be seen that when the post-oxidation temperature is too high, it will affect the uniformity of doping, resulting in reduced opening voltage, current and filling; when the post-oxidation square resistance is too high, it will affect the driving depth too deep, resulting in a significant reduction in opening voltage and current.
[0109] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0110] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a bottom cell of a TOPCon perovskite tandem cell, characterized in that: include: Step 1, double-sided texturing of the silicon wafer; Step 2, preparing a boron-doped layer on the first surface of the silicon wafer; Step 3, laser propulsion is performed on the metal contact area on the boron-doped layer to achieve heavy doping of the metal contact area; oxygen is then injected for post-oxidation, and after the post-oxidation is completed, the plating on the second surface of the silicon wafer is removed; after the post-oxidation is completed, the diffusion square resistance of the metal contact area is 250Ω / SP~400Ω / SP, and the diffusion square resistance of the non-metal contact area is 150Ω / SP~250Ω / SP; Step 4: After step 3, the silicon wafer is subjected to secondary texturing; a tunnel oxide layer and an intrinsic polysilicon layer are sequentially deposited on the second surface of the silicon wafer, and a phosphorus-doped layer is prepared on the intrinsic polysilicon layer; then, the first surface of the silicon wafer is de-poly plated and cleaned, and a passivation film layer and an anti-reflection film layer are deposited on the first surface and the second surface of the silicon wafer; Step five: print AgAl paste on the front anti-reflection film layer on the first surface, form a metal electrode after sintering, and obtain a TOPCon perovskite stacked battery bottom cell.
2. The preparation method according to claim 1, characterized in that The diffusion square resistance of the boron doped layer is 100Ω / SP to 200Ω / SP.
3. The preparation method according to claim 2, characterized in that: When preparing the boron doped layer, the diffusion temperature is 500°C to 900°C.
4. The preparation method according to claim 1, characterized in that: In laser propulsion, the laser parameters are set as: output power 10W~100W, pulse repetition frequency 200kHz~150kHz, laser spot diameter 5Pm~40Pm and laser beam speed 10000mm / s~30000mm / s.
5. The preparation method according to claim 1, characterized in that: In the post-oxidation, the oxidation temperature is 800°C to 1100°C.
6. The preparation method according to claim 5, characterized in that: In the post-oxidation, the oxidation time is 3000s to 6000s.
7. The preparation method according to claim 1, characterized in that: After secondary texturing, the height of the pile surface is 0.5-0.9 μm.
8. The bottom cell of the perovskite / TOPCon stacked cell prepared by the preparation method according to any one of claims 1 to 7.
9. A TOPCon perovskite tandem cell, characterized in that: Comprising the bottom cell of claim 9 and the perovskite top cell.
10. The perovskite / TOPCon tandem cell according to claim 9, characterized in that: The TOPCon perovskite stacked cell includes, from top to bottom, a front metal grid electrode Ag, an anti-reflection film layer SiNx, a transparent conductive layer ITO, an electron transport layer SnO2, a perovskite layer, a hole transport layer TiO2, a carrier recombination layer ITO and a bottom cell.
Citation Information
Patent Citations
Laser boron doped selective emitter TOPCon structure cell and preparation method thereof
CN110299422A
Method for manufacturing bottom cell of TOPCon perovskite laminated cell
CN119050198A
Selective emitter preparation method, selective emitter battery and preparation process
CN119170694A
Boron-diffusion selective emitter preparation method for topcon battery, and battery preparation process
WO2024120129A1
Cited By
Perovskite crystalline silicon laminated bottom cell structure, laminated cell and preparation method
CN120826067A
Perovskite crystalline silicon laminated cell, bottom cell and preparation method
CN121487377A
Laminated cell, preparation method thereof, cell preparation device and photovoltaic module
CN121815890A